2021
DOI: 10.3390/ijerph18105107
|View full text |Cite
|
Sign up to set email alerts
|

Association of Child Mental Health with Child and Family Characteristics in Rural China: A Cross-Sectional Analysis

Abstract: Assessing the mental health problems encountered by school children and understanding the contributing factors are crucial to inform strategies aimed at improving mental health in low-resource contexts. However, few studies have investigated the mental health problems among disadvantaged children in poorer countries. This study examines the prevalence of mental health problems in rural China and their association with child and family characteristics. The study uses survey data from 9696 children in 120 rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…This may be attributed to the Beirut blast which caused children from the surrounding areas to experience multiple psychological impacts [48-50]. A higher mean of prosocial problems in children was also more commonly reported by participants having intermediate and elementary education levels, similar to the ndings of Wang et al (2021) [16] where higher SDQ total di culties scores were associated with having a parent with a lower education level. Having parents with a higher educational level may be thus a protective factor for children's mental health [51].…”
Section: Discussionmentioning
confidence: 77%
“…This may be attributed to the Beirut blast which caused children from the surrounding areas to experience multiple psychological impacts [48-50]. A higher mean of prosocial problems in children was also more commonly reported by participants having intermediate and elementary education levels, similar to the ndings of Wang et al (2021) [16] where higher SDQ total di culties scores were associated with having a parent with a lower education level. Having parents with a higher educational level may be thus a protective factor for children's mental health [51].…”
Section: Discussionmentioning
confidence: 77%
“…In assessing for abnormal scores, we found that they were higher for conduct problems (8.5%) than in the other domains, and abnormal total difficulties scores reached 5.1% among our in-school participants. In comparison, in a study among adolescents in the Chinese context, Wang et al found that a higher proportion of the participants (17.9%) had a high total difficulties score [28]. Data from the Indian subcontinent showed that more than a tenth of in-school adolescents reported abnormal scores in the SDQ in a study by Harikrishnan, U. and Sailo, G.L.…”
Section: Discussionmentioning
confidence: 92%
“…36 The mean total difficulties score (12.60) was also higher than that found in a sample including both urban and rural adolescents in the northeastern Chinese province of Liaoning (10.96) and was on par with a rural sample in the southeastern province of Jiangxi (12.93). 37,38 One potential reason for the relatively high share of abnormal behaviors experienced by our sample might be that more than a third of the adolescents were left-behind children (with no parents at home due to migration to cities for work) or partially left-behind children (with one parent not at home). Past literature has demonstrated that left-behind children -with lower levels of social support at home -are significantly more likely to be at risk of mental health problems than their peers.…”
Section: Discussionmentioning
confidence: 99%